1986
DOI: 10.1007/bf00174355
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone does not affect cigarette smoking

Abstract: In order to provide information about the hypothesis that endogenous opioids mediate the reinforcing properties of cigarette smoking, the present study examined the effects of naloxone, an opioid antagonist, on cigarette smoking in seven normal volunteers. The study used experimental procedures that had previously been shown sensitive for detecting the effects of other drugs, (including a nicotine antagonist) on smoking. Isolated subjects smoked their regular brand of cigarettes freely in a naturalistic labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 15 publications
4
37
0
1
Order By: Relevance
“…However, this hypothesis will require further study and confirmation, because the number of cigarettes smoked per day does not reliably predict nicotine levels [10]. Peripheral blood concentrations of b -end do not always correlate highly with central concentrations [6,21], and use of the opioid antagonist naloxone does not appear to modify smoking [15], although some authors have reported positive results [9,19]. Plasma concentrations of cortisol also differed between the groups of smokers we studied; the differences were greater between moderate and heavy smokers than between control subjects and light smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis will require further study and confirmation, because the number of cigarettes smoked per day does not reliably predict nicotine levels [10]. Peripheral blood concentrations of b -end do not always correlate highly with central concentrations [6,21], and use of the opioid antagonist naloxone does not appear to modify smoking [15], although some authors have reported positive results [9,19]. Plasma concentrations of cortisol also differed between the groups of smokers we studied; the differences were greater between moderate and heavy smokers than between control subjects and light smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent human clinical trials with naloxone or the longer acting opioid receptor antagonist naltrexone showed inconsistent results both in the degree that these agents diminished tobacco smoking as well as on their behavioral effects (Nemeth-Coslett and Griffiths, 1986;Gorelick et al, 1988;Sutherland et al, 1995;Wewers et al, 1999). Aceto et al (1993) examining the analgesic effects of nicotine in rodents, and Pomerleau (1998) in a review of both human and animal data, postulated that nicotine produced both pro-and antiopioidergic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the positive reinforcing properties of nicotine could be hypothesized to be modulated by activation of enkephalin neurons along parallel reward systems to the dopamine system (i.e., dopamine-independent systems) (Houdi et al, 1991;Pomerleau & Pomerleau, 1984). Nevertheless, pharmacological studies in humans investigating the effects of naloxone, an opioid receptor antagonist on smoking behavior, have yielded inconsistent results (Karras & Kane, 1980;Nemeth-Coslett & Griffiths, 1986).…”
Section: Opioid Peptide-dopamine Interactionsmentioning
confidence: 99%